Servant Leadership and Teacher Burnout in Islamic Educational Institutions: A Systematic Literature Review on Teachers’ Holistic Well-Being: - Nafi, Ahnaf; Mushoffa, Nabil; Pranoto, Ahmad Hadi (SENTRI: Jurnal Riset Ilmiah, 2025)
Work-related burnout, or “teacher burnout,” has become an increasingly prominent issue in Islamic educational institutions, particularly in madrasahs and private schools that bear the dual burden of administrative demands, accreditation pressures, and expectations for character development based on religious values. Amid the dominance of leadership studies that tend to be results-oriented and top-down in nature, servant leadership offers an alternative paradigm that places service, empathy, and teacher empowerment at the core of leadership practice. This article was compiled using a Systematic Literature Review (SLR) approach following the PRISMA protocol to map, synthesize, and evaluate scientific literature on servant leadership and teacher burnout in Islamic educational settings published between 2021 and 2026. The search was conducted in the Google Scholar, Garuda, and DOAJ databases, yielding a number of relevant articles that were subsequently screened based on thematic and methodological eligibility criteria. The results of the study indicate that the dimensions of empowerment, humility, and emotional healing are the three dimensions of servant leadership most consistently associated with a reduction in teachers’ emotional exhaustion and depersonalization. Furthermore, the integration of servant leadership with Islamic prophetic values such as shiddiq, amanah, and the spirit of sincere service strengthens teachers’ holistic well-being, which encompasses physical, mental, and spiritual dimensions alike. These findings have important implications for madrasah principals and foundation administrators in designing a leadership model that is humanistic, protective, and grounded in Islamic values.